1995
DOI: 10.1136/gut.36.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of familial disease in primary biliary cirrhosis.

Abstract: Susceptibility to primary biliary cirrhosis (PBC) may be partly inherited although instances of PBC within families are only infrequently described. The records of 736 patients with PBC seen over a 25 year period were examined to identify those with a positive family history. Ten patients originating from eight families were identified, giving a frequency of 1.33%. They comprised mother and daughter pairs; in two families both mother and daughter had been seen at our clinic. The daughters presented at an earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 22 publications
8
52
1
3
Order By: Relevance
“…We found that 2% of PBC cases had first-degree relatives with PBC, which was lower than the proportion observed in some of the other studies. [18][19][20] One of these studies was also based in the Northeast of England, and reported that the prevalence of PBC among first-degree relatives was 5%. However, the study by Jones et al 20 had few cases in common with the current study, because of a different choice of study area and period.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 2% of PBC cases had first-degree relatives with PBC, which was lower than the proportion observed in some of the other studies. [18][19][20] One of these studies was also based in the Northeast of England, and reported that the prevalence of PBC among first-degree relatives was 5%. However, the study by Jones et al 20 had few cases in common with the current study, because of a different choice of study area and period.…”
Section: Discussionmentioning
confidence: 99%
“…Twin and family studies strongly suggest a genetic predisposition to PBC. 56,57 Variations in immunoregulatory genes, such as human leukocyte antigen class II (HLA-II) alleles, proinflammatory cytokines (TNF-␣ and IL-1␤), CTLA-4, and vitamin D receptor, influence disease susceptibility. [58][59][60] Moreover, genetic polymorphisms may influence disease progression.…”
Section: Gene Polymorphisms Influencing Liver Fibrosis In Humansmentioning
confidence: 99%
“…Family members of patients with PBC have a higher risk of developing the disease, and the occurrence of multiple cases within the same family is referred to as 'familial PBC' 7 presenting variable frequency rates, possibly following a geoepidemiological pattern (Table 1). Studies from the UK indicate that such frequency ranges between 1 and 2.4%, 8,9 possibly increasing over the past decade, likely for the awareness of physicians and novel diagnostic tools.…”
Section: Familial Pbcmentioning
confidence: 99%